Mass distribution campaign of long-lasting insecticidal nets (LLINs) during the COVID-19 pandemic in Uganda: lessons learned - Herbert Bush Aguma; Medard Rukaari; Rukia Nakamatte; Pamela Achii; Joel Tutu Miti; Solomon Muhumuza; Mariam Nabukenya; Jimmy Opigo; Martin Lukwago (Malaria Journal, 2023)
Abstract Background Uganda implemented its third mass campaign to distribute long-lasting insecticidal nets (LLINs) in 2020 during the COVID-19 pandemic. This context necessitated modification of implementation guidelines. The mass campaign's objective was to ensure that at least 85% of the targeted population had access to LLINs. Methods Revised implementation guidelines were followed while conducting the LLIN distribution campaign. Lessons learned were captured from documented activities and reports. Results A total of 27,789,044 mosquito nets were distributed in 11,287,392 households, with an average of 5.1 persons per household. Household coverage of the LLIN distribution was 94.1%. The 2020/2021 campaign design was modified to follow COVID-19 Standard Operating Procedures (SOPs). These included using Personal Protective Equipment (PPE), e-platforms for training and briefing meetings, electronic data management systems and door-to-door household registration and distribution of LLINs. Conclusions Campaign modifications due to the COVID-19 pandemic were effective in implementing mass distribution of LLINs despite the disruptions and restrictions. The campaign’s net coverage far exceeded its objective. Electronic data management was critical in monitoring and reporting distribution activities.